G473 A review of the neurology consults of the clinical ethics service at a tertiary children's hospital. (12th March 2018) - Horne, A; Prabhakar, P; Brierley, J; Aylett, S
Abstract : Background: The medical care of children with severe neurological disease, poses a number of ethical challenges; perhaps due to the lack of a cure, use of experimental treatment, and life limiting nature. When such ethical dilemmas arise, the clinical team and family may benefit from Clinical Ethics Support to help a consensus emerge on the best course of action for the child. At this centre, a Rapid Case Review Service (RCRS) can occur within hours, but frequently days to review issues with the child's multidisciplinary team and parents. Little research has been carried out on this cohort's ethical challenges, and use ethics. Objectives: Understand medical, ethical and legal aspects of neurology RCRS consult and its role in addressing ethical problems faced Methods: Of 44 RCRS between 2012–2016, 11 were identified as having had a primary neurological disorder Data obtained from RCRS referral form; Meeting minutes and Electronic patient records then categorised into 4 main variables: Demographics, Medical, Ethical and Legal. Confidentiality upheld by removing any patient identifiers Results: Demographics: Age 1–16 years (median 9); Medical: Average of 4 clinical diagnoses (range 2–5) Main categories: Neurolgical (5) (cerebral palsy and hydrocephalus); Neuro-metabolic (Leigh's syndrome, Pompe disease); neuromuscular (DMD, SMA 1). Support teams: Palliative Care (10); External (8); Social Care (8); Psychology (6). Other concurrent conditions: Epilepsy (4); Neurodevelopmental delay (2); Learning disability (3). All had life limiting conditions. 4 had died by time of review (3 treatment withdrawal); 6 returned home of which 2 were now attending school. Ethical issues: Conflicts between the clinical team and parents (6) RCRS recommendations: Involve palliative care and discuss DNAR; Seek second opinions regarding management; create a care plan with parents' involvement Ethical challenges Limitation of treatment 3; Withdrawal of treatment 2; Discharging home with TPN 2; Refusal of consent for surgery 1; Escalation of pain medication 1; Burden of treatment 1; Experimental treatment 1. Legal issues: One case was taken to court, seeking approval to withdraw artificial hydration on the grounds of child's best interest Discussion: Neurology consults made up 25% of the RCRS. They pose a particular challenge, with complex, often incurable disease, with either no evidence-based treatments or only palliative therapies available. So, ethical dilemmas regarding treatment and end of life decisions are common. The associated neuro-disability, and life-limiting aspect means social care and palliative care should be involved early on. Furthermore, discussions around care plans and DNAR should be prioritised. The RCRS has a vital role in helping resolve conflict between the clinical team and parents, and supporting them to come to a consensus on management. It is rare that a court application is required. Future improvements may involve routine referrals to the RCRS, focused ethics' training for neurology clinicians, and prerequisite criteria for referral (e.g. having a second opinion and care plan).